In vitro antioxidant and antibacterial activities of Ajuga integrifolia leaf extracts obtained with different solvents - Workineh Mengesha Fereja; Wakuma Debessa Geleta; Engida Desalegn; Mitiku Moaneanda; Adugna Abdissa; Firehiwot Belyneh Usamo (BMC, 2024)
Abstract Background Many diseases are increasingly recognized as public health concerns worldwide because of the increasing incidence of multidrug-resistant bacteria. Recently, interest in the use of indigenous medicinal plants to treat infectious illnesses has increased, highlighting the need to find new bioactive phytochemicals. Ajuga integrifolia is a plant commonly utilized in traditional drugs to treat a wide range of diseases, although its effectiveness has not been scientifically validated. The present study aimed to evaluate the total phenolic and flavonoid contents and assess the biological activities of A. integrifolia leaf extracts produced via different solvent systems. Methods Soxhlet extraction was employed to obtain crude extracts from different solvents (methanol, ethanol and water). The 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric-reducing power assays were used to measure the antioxidant activity, and the antibacterial activity of the extract was evaluated on the basis of its minimum inhibitory concentration (MIC) against two gram-negative bacteria (Escherichia coli (ATCC-25922) and Pseudomonas aeruginosa (ATCC-43495)) and two gram-positive bacteria (Staphylococcus aureus (ATCC-25923) and Streptococcus pyogenes (ATCC-19615)) via the agar disk-diffusion technique. Results A significant amount of total phenolic content (TPC) and flavonoid content (TFC) were present in all the extracts. The extracts presented powerful antioxidant activity in all the assays. The disc diffusion and MIC results revealed the ability of the methanol and ethanol extracts of A. integrifolia leaves to inhibit S. aureus growth at a concentration of 3.125 mg/mL. However, the water extracts were ineffective against E. coli and P. aeruginosa. Conclusions These findings indicate that A. integrifolia leaf extracts have reasonable biological activities. These findings underscore the importance of A. integrifolia leaves as a source of health benefits.